Trade in health services: an analytical framework - Patricia Waeger (Kiel Institute for the World Economy (IfW), 2007)
The present paper deals with a topic that pertains to Health Economics as well as to Trade Theory - Trade in Health Services. It is intended to deliver an analytical framework for the assessments of this new sector of international trade which takes into account both the 'general welfare aspects' and the effects for the achievement of general 'health system goals'. While to former will be scrutinized by the subcategories allocation, accumulation and location effects, the latter is aligned with the OECD Health System Performance Framework which mentions three major health system goals that are 'Health Improvement & Outcome', 'Responsiveness & Access' and 'Financial Contribution & Health Expenditures'. For this purpose trade in Health Services is split up according to the four modes of service supply introduced by the General Agreement of Trade in Services (GATS). For each mode examples are enclosed and the current level of trade is analysed. It is also examined what are the major obstacles for trade in these modes and what liberalization perspectives are given. The subsequent discussion and plausibility considerations of how each mode may contribute to improve efficiency as well as equity in national health systems is a systematic starting point for further research. It provides a first insight in how trade in Health Services could help to overcome resource constraints in national health systems as well as allude to the potential risks of which sight shouldn't be lost.
Keywords: 330; Gesundheitswesen; Gesundheitsversorgung; Internationaler Dienstleistungsverkehr; Gesundheitskosten; OECD-Staaten